Minimizing the surgical approach for a rare disease: transanal endoscopic microsurgery for rectal schwannoma. Issue 6 (December 2019) - Guaglio, Marcello; Belli, Filiberto; Cesa Bianchi, Alessandro; Sorrentino, Luca; Battaglia, Luigi
Objective: Rectal schwannomas are extremely rare tumors and their surgical treatment is widely variable in literature. Transanal endoscopic microsurgery (TEM) approach could be a reasonable option for such lesions, offering an organ-sparing strategy, but evidence is scarce. Methods: We report a 69-year-old man with a rectal submucosal lesion at 10 cm from the anal verge, treated by TEM. A systematic literature review on surgical approaches in rectal schwannoma was performed. Results: The patient was successfully treated by TEM, with adequate excision of the submucosal lesion. Histopathology revealed a rectal schwannoma. No recurrence was found at 1-year endoscopic follow-up. Previous studies reported 23 cases of rectal schwannoma and several treatment options, but only 2 cases were treated by TEM. Anterior rectal resection was generally adopted in cases of large, symptomatic masses with inconclusive preoperative biopsy, while lesions with features suggestive of stromal tumors were preferentially treated by endoscopy or, if located in distal rectum, by transanal approaches. Conclusions: An organ-sparing minimally invasive approach should be the standard of care for rectal schwannomas. TEM could extend the indication for their endoscopic treatment, providing adequate excision even for larger schwannomas of the middle–upper rectum.